Covalent coupling of ionic liquid to carbon nanotubes: preparation and tribological properties. Issue 1707 (4th June 2014) - Taaber, Triinu; Põhako-Esko, Kaija; Joost, Urmas; Külasalu, Kadi; Antsov, Mikk; Antonov, Maksim; Veinthal, Renno; Saal, Kristjan; Lõhmus, Rünno; Mäeorg, Uno
ABSTRACT: A new approach for functionalising oxidised MWCNTs using hydroxylated imidazolium bromide via esterification reaction is reported. The bromide anion of a functionalised MWCNTs was exchanged with bis(trifluoromethanesulfonyl) imide (TFSI) through a metathesis reaction to improve its solubility in the IL medium. Composite was characterized with IR, XPS, EDX and TGA analysis, which clearly confirmed that the MWCNTs were functionalized with IL. For potential application as lubricant, the tribological properties of the IL-functionalised MWCNTs (MWCNT-IL) were also evaluated. It was confirmed that even low concentrations of MWCNT-IL composite in ILs causes a significant improvement in the anti-wear and friction properties.